A case report of right ventricular outflow tract obstruction caused by B-cell lymphoma: a rare presentation in an adult patient with pulmonary atresia. Issue 10 (7th October 2021) - Chatta, Payush; Qureashi, Mohammad; Plato, Steven; Kirk, Shannon; Yau, David; Kheiwa, Ahmed; Parwani, Purvi; Razzouk, Anees
Abstract: Background: Right ventricle outflow tract (RVOT) dysfunction is a common long-term complication in adult patients with pulmonary atresia/ventricular septal defect (PA/VSD). Common causes include valve thrombosis, stent fractures, and graft calcification. We present, to the best of our knowledge, the first case of malignant invasion of a Gore-Tex conduit, causing severe right ventricle (RV) failure. Case summary: A 30-year-old woman with a history of PA/VSD with major aortopulmonary collateral arteries (MAPCAs) presented with worsening dyspnoea and exercise intolerance. In infancy, she underwent unifocalization of the right- and left-sided AP collaterals utilizing an 18 and 16 mm Gore-Tex graft, respectively. At age 7, she had surgical repair with VSD patch closure and placement of a 20 mm right ventricle-pulmonary artery (RVPA) homograft connected to a 20 mm Gore-Tex graft with linkage to the previously placed right and left unifocalization grafts. A transthoracic echocardiogram revealed a severely dilated RV and a heavily calcified RVOT conduit with severe stenosis. Cardiac computed tomography showed a stenotic RVPA conduit with calcified mural mass. She underwent surgical revision of the RVPA conduit with thromboendarterectomy of bilateral pulmonary arteries. Pathology of the removed conduit revealed fibrin-associated Epstein–Barr virus-positive diffuse large B-cell lymphoma (FA DLBCL). Discussion: One prior case report has demonstrated invasion of DLBCL involving an aortic synthetic tube graft. However, malignant invasion of the RVOT Gore-Tex conduit has yet to be reported. Pathological review can be essential in guiding management. Malignant invasion of Gore-Tex conduits is a rare phenomenon, but one that should be closely monitored following repair of the RVOT.